Rapid isolation and detection of Escherichia coli O157H7 by use of rainbow agar O157 and PCR assay - Son, Radu; Gulam, Rusul; Ooi Wai, Ling; Endang, Purwati; Maimunah, Mustakim; Samuel, Lihan (UPM, 2000)
This study has evaluated the use of a commercially available Rainbow agar O157TM and polymerase chain reaction (PCR) assays for the detection of Shiga-like toxin producing Escherichia coli and to serotype E. coli O157:H7 from raw meat. The Rainbow agar O157TM was found to be selective and sensitive for the screening of the E. coli O157 from artificially and naturally contaminated meat samples. Shiga-like toxin producing E. coli were identified with two primer pairs that amplified fragments of the SLT-I (384 bp) and SLT-II (584 bp). E. coli O157:H7 was serotyped with a primer pair specified for the H7 flagellar gene, which amplify specific DNA fragments (625 bp) from all E. coli O157:H7 strains. The use of Rainbow agar O157TM described allows for the presumptive isolation of E. coli O157 in 24 hours. Identification and confirmation of the presumptive isolates as E. coli O157:H7 by PCR assays require additional 6-8 hours. The above-mentioned screening and identification procedures should prove to be a very useful method since it allows for the specific detection of E. coli O157:H7.